Effects of MicroRNA on Regulatory T Cells and Implications for Adoptive Cellular Therapy to Ameliorate Graft-versus-Host Disease - Keli L. Hippen; Michael Loschi; Jemma Nicholls; Kelli P. A. MacDonald; Bruce R. Blazar (Frontiers in Immunology, 2018)
Regulatory T cells (Tregs) are key mediators of the immune system. MicroRNAs (miRNAs) are a family of ~22 nucleotide non-coding RNAs that are processed from longer precursors by the RNases Drosha and Dicer. miRNA regulates protein expression posttranscriptionally through mRNA destabilization or translational silencing. A critical role for miRNA in Treg function was initially discovered when both Dicer and Drosha knockout (KO) mice were found to develop a fatal autoimmune disease phenotypically similar to Foxp3 KO mice.